Specters of Sex. Tracing the Tools and Techniques of Contemporary Music Analysis - Danielle Sofer (Zeitschrift der Gesellschaft für Musiktheorie)
Music has often served as a vehicle for sexual expression. But within a musical context saturated with many sonic phenomena, music-analytical tools can be limited in their ability to pinpoint evidence of sex acts, pleasure, or satisfaction. Centering on sonic experience and perception, this article challenges the common trope of the disembodied and disinterested music theorist by proposing that, rather than neglecting sexual discourses, like-minded music theorists have instead established a veritable field founded on the commonly-held belief that sex and music are (in some cases) interchangeable. The article proposes that the meta-theorization of these engagements constitutes a discursive “social epistemology” thereby positioning such diverse contributions as part of the core music-theoretical “standard” of what was once called “mainstream music theory.”